Effect of integrated application of organic manures on soil parameters and growth of mungbean (Vigna radiata) - SHUKLA, L; TYAGI, S P (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2004–7 in summer season to ascertain the effect of 2 organic inputs, viz enriched compost and vermicompost applied @ 2 tonnes/ha, on selected soil parameters for soil health, growth and nodulation of ‘Pusa Ratna’ mungbean [Vigna radiata (L.) Wilczek]. The beneficial effects were compared not only to soils but also the growth of the crop without organic inputs. Organic matter, like vermicompost and enriched compost enhanced soil physical properties and plant nutrients (N, P and K) at the time of crop establishment and early growth. Incorporation of vermicompost and enriched compost before sowing had a greater beneficial impact, especially on physical properties of soil. The added organic materials, like vermicompost and enriched compost increased germination growth of shoots, roots and enhanced nodulation, the slightly greater benefits were derived with vermicompost as compared to enriched compost. The selected microorganisms used were Rhizobium, a symbiotic nitrogen fixer and phosphate-solubilizing bacteria which helps in solubilization of fixed phosphorus.